Cirrhosis : a practical guide to management - Lee, Samuel S., 1954-; Moreau, Richard, 1951- (Chichester, West Sussex ; Hoboken, NJ : Wiley-Blackwell, 2015)
Cirrhosis: a practical guide to management providesgastroenterologists and hepatologists with an up-to-date clinicalguide presenting the very best evidence-based practice in thediagnosis, treatment and management of liver cirrhosis and its manycomplications. Designed to offer practical guidance at alltimes, it provides doctors with an extremely useful tool in theclinical setting, with each chapter featuring diagnostic/managementalgorithms, key points and other pedagogic features. Divided into 2 parts, a diagnosis and pathophysiology section and amanagement of complications section, key topics.
Morphologic changesHemodynamic changes; MR elastography; Other imaging techniques; References; 4. Histology/pathology; Introduction; Cirrhosis: a pathologic spectrum; Fibrosis: extracellular accumulation of matrix components; Vascular changes; Parenchymal nodules: etiologic features; Cirrhosis: an evolving concept; Cirrhosis: a preneoplastic condition; Cirrhosis: a place for biopsy?; References; 5. Fibrosis and fibrogenesis; Introduction; Mechanism of liver fibrosis in hepatitis B and C; Diagnosis of liver fibrosis by imaging; Diagnosis of liver fibrosis by laboratory tests.
Includes index.
Includes bibliographical references and index.
Print version record and CIP data provided by publisher.
Keywords: Liver -- Cirrhosis; Liver Cirrhosis -- diagnosis; Liver Cirrhosis -- therapy; Liver Diseases -- complications; Liver cirrhosis -- Diagnosis; Liver cirrhosis -- Therapy; Liver diseases -- Complications; HEALTH & FITNESS -- Diseases -- General; MEDICAL -- Clinical Medicine; MEDICAL -- Diseases; MEDICAL -- Evidence-Based Medicine; MEDICAL -- Internal Medicine; Liver -- Cirrhosis; Electronic books